Description of a new species of the genus Hulecoeteomyia (Diptera: Culicidae) from Meghalaya, India - Natarajan, R.; Rajavel, A.r.; Jambulingam, P. (Zootaxa, 2016)
Female and male adults, female and male genitalia, pupa and larva of Hulecoeteomyia cherrapunjiensis, a new mosquito species, are described from Meghalaya, India. Keys to separate larvae and adults are provided.